Production planning and control - Bolton, W. (Longman Scientific & Technical, 1994)
The planning and control of the production process represents a fundamental part of modern manufacturing technology. This book provides an essential introduction to the basic principles involved and is specially written for BTEC HNC/D programmes in mechanical and production engineering. The aim is to give the reader a practical and comprehensive appreciation and understanding of the ways in which manufacturing companies are organised; the nature and diversity of engineering products; the organisation of production and the planning and control of production. Production Planning and Control covers the BTEC units Control of Manu639-5 Manufacture U38/188 and Production Planning and Control U38/189.